Social Media Marketing : Theories and Applications - Dahl, Stephan (SAGE Publications, Ltd. (UK), 2021)
Helping you make the connections between the theory and practice of social media marketing, this third edition of the popular text has been updated to include technological advances in practice such as AI and virtual marketing, alongside a brand-new chapter on the rise of influencer culture and marketing.  Examples and case studies throughout help you to contextualise the text through popular brands and platforms such as Instagram, Dunkin Donuts, Amazon and also political marketing for social movements such as Extinction Rebellion.  This text is essential reading for all marketing students, researchers and practitioners today.